2022
DOI: 10.1115/1.4053276
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Spot Welding of Additively Manufactured Maraging Steels—Part II: Failure Behavior

Abstract: Application of maraging steels via selective laser melting process in the automotive industry was unavoidably involved in the resistance spot welding with conventional steels. Due to the rapid cooling rate of welding process, selective laser melted maraging steels with unique chemical components and stack microstructure could induced the different microstructural evolution, resulting in the complicated fracture behavior in the spot welds. This paper developed a FEA model to predict the fracture mode of spot we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Element types used in the model were C3D8R and C3D10 in different regions for a balanced computational efficiency and accuracy. The authors' previous work 18 provides a detailed description of the FE modeling method and the local material properties used in the current study.…”
Section: Material Specimen and Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Element types used in the model were C3D8R and C3D10 in different regions for a balanced computational efficiency and accuracy. The authors' previous work 18 provides a detailed description of the FE modeling method and the local material properties used in the current study.…”
Section: Material Specimen and Experimental Proceduresmentioning
confidence: 99%
“…Therefore, it is crucial to investigate the effects of printing orientation on the microstructure and mechanical properties of spot welds for SLMed MS1 parts, particularly when welded to conventionally produced steel to form dissimilar spot welds, such as the MS1 to DP600 spot weld. In our previous work, 11,18 we studied the weld nugget formation mechanism in MS1 RSWs with sheets of varying printing orientation, which revealed that the different material properties of maraging steels affect the fracture displacement in the tensile force-displacement curve of spot welds. Furthermore, the effect of printing orientation on the fracture mode and strength of MS1 RSWs were investigated, and results demonstrated that the printing orientation has no significant impact on the fracture mode and strength of spot welds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation